THE EFFECT OF TEACHING AT THE RIGHT LEVEL (TARL) APPROACH ON LITERACY SKILLS OF PRIMARY SCHOOL STUDENTS - Ahmad; Syarifuddin; Fuaduddin; Riningsih; Iriyanti (AULADUNA: Jurnal Pendidikan Dasar Islam, 2024)
Abstract This study investigates the use of the Teaching at the Right Level (TaRL) approach to enhance students’ reading literacy skills, specifically by tailoring learning methods to individual ability levels. The research utilized a quasi-experimental design and collected data through tests, observations, and interviews. The study focused on grade I students at MIN Kota Bima, with grade I D serving as the control group and grade I E as the experimental group that received the TaRL learning intervention. Descriptive and inferential statistics, specifically the independent sample t-test, were used to analyze the data. The findings indicated that the TaRL approach had a positive impact on students’ literacy skills. Implementing the TaRL approach is an effective way to address the issue of low reading literacy skills in students.